Chromatographic and Spectroscopic Analysis of Flower Pigments in Mirabilis Jalapa - Aishwarya Patil,; Nikita Sawant,; Pratibha Patil,; Vidya Patil, (The Bioscan, 2025)
The growing popularity of natural colorants derived from plant-based sources can be attributed to customer's increased health awareness. Pigment extraction is one of the most crucial procedures among the several involved in creating natural colorants. Because natural pigments are good for the environment, they are interesting. The present studies have been conducted on chromatographic and spectroscopic analysis of Mirabilis jalapa flower pigment. Distilled water is used as a solvent to extract pigment, producing the maximum results. Analytical protocols like Thin Layer Chromatography (TLC), and UV-visible spectroscopy were carried out. The pigments from floral extracts showed widespread absorption peaks in the visible spectrum, according to UV-visible experiments. Spectral patterns were used to analyze the pigment’s color stability. The pharmacological effects of Mirabilis jalapa flower pigments are enlisted and described.